Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2014
DOI: 10.14252/foodsafetyfscj.2014015
|View full text |Cite
|
Sign up to set email alerts
|

Possible Carcinogenic Mechanisms Underlying Renal Carcinogens in Food

Abstract: Some chemicals contained in foods originating from a variety of sources including natural plants, food additives, residual pesticides, mycotoxins and by-products created during food processing and/or cooking have previously been demonstrated to be carcinogenic at various sites in rodents. This review focuses on reported renal carcinogens in natural products such as d-limonene and aristolochic acid (AA), food additives such as potassium bromate (KBrO 3 ) and madder color (MC), as well as mycotoxins such as ochr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 116 publications
(149 reference statements)
0
3
0
Order By: Relevance
“…Misincorporations caused by translesion synthesis across LdG by major TLS DNA polymerases tested here are T or G by pol η and T by pol ι (Figure 2B and Table S2 of the Supporting Information). These mispairs can potentially lead to G to A transitions and G to C transversions, which have been observed in LuP-treated rats, 16 although they are considered as minor mutations relative to the three major mutations noted earlier.…”
Section: Resultsmentioning
confidence: 93%
See 1 more Smart Citation
“…Misincorporations caused by translesion synthesis across LdG by major TLS DNA polymerases tested here are T or G by pol η and T by pol ι (Figure 2B and Table S2 of the Supporting Information). These mispairs can potentially lead to G to A transitions and G to C transversions, which have been observed in LuP-treated rats, 16 although they are considered as minor mutations relative to the three major mutations noted earlier.…”
Section: Resultsmentioning
confidence: 93%
“…Madder root has also been used as an herbal medicine for treating kidney and bladder stones , and urinary disorders . In Japan and Korea, madder color had been used as a natural food colorant and additive, and such use was banned in 2004 in both countries due to its toxicity in experimental animals. In rats, madder root exerts carcinogenicity; , however, in humans madder root is classified as Group 3 (i.e., not classifiable as to its carcinogenicity to humans) by the International Agency for Research on Cancer . The reason for the low carcinogenic risk of lucidin in humans remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…[ 79 ] Such miscoding events may lead to the G to C transversions as well as G to A transitions. [ 98 ] Mass spectral analyses was carried out to gain more details on the frameshift generation by hpol κ‐mediated TLS across LdG adduct. [ 99 ] These studies revealed error‐free TLS past LdG by hpol κ at physiological concentrations of dNTPs.…”
Section: Tls Studies Of Specific N2‐dg Damaged Dnasmentioning
confidence: 99%